Assessment Of Pulmonary Functions In Overweight Adults- A Case Control Study - RAMYA K; MUKUNDAN A (International Journal of Pharma and Bio Sciences, 2015)
Obesity is considered as the main risk factor for many systemic disorders. In recent years, studies have also proved the influence of increasing BMI in impaired lung functions .Simple clinical anthropometric measures may be conveniently used to assess obesity along with spirometry for lung function assessment. Aim of this study is to determine and compare FVC, FEV1, FEV1/FVC and PEF among normal and overweight individuals irrespective of gender. This is a case control study. Subjects were selected according to the inclusion and exclusion criteria with a sample size of 100, using a pretest proforma. Weight, height and lung functions were measured for each participant using standard methods. Then the data obtained was analyzed using unpaired t- test. Significant difference is observed in all the four parameters (Forced vital capacity (FVC), forced expiratory volume in first second (FEV1), %FEV1, peak expiratory flow (PEF) with p value <0.05, when compared between normal and overweight individuals irrespective of gender. Inverse relationship existing between BMI and lung functions proves that, overweight also acts as one of the risk factor for defective lung functions.